Evaluating the Impact of Artificial Intelligence Enhanced Augmented Reality Tools on Social Interaction in Learners with Autism Spectrum Disorder - Elegbeleye, Femi; Olusegun Oguntona; Ife Elegbeleye; Jose Lukose (AI Society & STMIK Indonesia, 2025)
Autism Spectrum Disorder (ASD) is a cognitive developmental condition characterized by persistent deficits in social communication and interaction, alongside restricted and repetitive patterns of behavior. The global prevalence of ASD is estimated at approximately 1% in the general population, with higher rates observed in specific demographic groups. Individuals with ASD often experience challenges in interpreting social cues, initiating interactions, and participating in group settings, which can impede their academic and social development. This study examines how Augmented Reality (AR) and Artificial Intelligence (AI)-based interventions can complement or improve the social communication skills and behavioral patterns of individuals with ASD. A systematic literature review (SLR) was conducted, focusing on peer-reviewed studies published between 2019 and 2024, to assess the efficacy and practicality of these technologies in educational environments. The analysis covers engagement of visual boards, smartphones, tablets, and AR glasses, which are increasingly integrated into pedagogical strategies to enhance the learning experiences of students with ASD. The results demonstrate that AI-enhanced AR-based interventions significantly outperformed traditional teaching methods, with notable improvements in social interaction (70% vs. 50%), emotional recognition (60% vs. 40%), engagement (80% vs. 55%), communication skills (75% vs. 45%), and behavioral outcomes (65% vs. 50%). These technologies appear to support the development of social skills by providing interactive, personalized, and visually enriched learning environments. The outcomes of this research highlight the potential of AI-enhanced AR to complement traditional teaching methods, offering valuable insights for educators, therapists, and policymakers seeking practical approaches to support learners with ASD. Further empirical research is recommended to validate these findings across diverse educational settings